Comparative Analysis of Support Vector Machine Regression and Gaussian Process Regression in Modeling Hydrogen Production from Waste Effluent - Hossain S.S.; Ayodele B.V.; Ali S.S.; Cheng C.K.; Mustapa S.I. (MDPI, 2023)
activated sludge; chemical oxygen demand; effluent; Gaussian method; support vector machine